A sixteenth century Portuguese report concerning an early Javanese world map Relatório português do século XVI descreve mapa-múndi antigo de origem javanesa - Benjamin B. Olshin (História, Ciências, Saúde: Manguinhos)
In the sixteenth century, there were numerous voyages of discovery in the oceans of the world, expanding European understanding and influence. These explorations, and in particular the knowledge they created, have tended to overshadow other ventures into the unknown. Not just the Europeans, but other cultures as well, navigated the seas and accumulated geographical information, putting together their own ideas about the distribution of the lands and seas around the globe. Arab and Asian seafarers plied the oceans in trade and exploration, and created maps and geographical texts. These maps and texts, however, are not as numerous as a scholar might wish. The Asian maps, particularly early ones, are few in number, and these are virtually all Chinese and Korean creations, world maps based on traditional religious concepts of a circular landmass. There are few maps based on actual navigation. But an early sixteenth-century Portuguese document gives a brief description of a Javanese map, which apparently showed much of the world. It also depicted the routes of the navigations of the Chinese and other Pacific peoples. The map itself has been lost, but we read of it in a letter from the Portuguese admiral Afonso de Albuquerque to his king, Dom Manuel, dated 1 April 1512. No século XVI, várias viagens de descobrimento expandiram a influência e o reconhecimento europeus. Essas expedições marítimas, e em particular o conhecimento que geraram, ofuscaram outras aventuras pelo desconhecido. Outros povos navegaram pelos oceanos, acumularam informações e organizaram suas próprias idéias sobre a distribuição de terras e mares. Navegadores árabes e asiáticos criaram mapas, cartas náuticas e textos geográficos expondo suas descobertas. Esses mapas, no entanto, não são tão numerosos. Os asiáticos, particularmente os mais antigos, são poucos e quase todos originários da China e Coréia, e baseavam-se em conceitos religiosos tradicionais e na idéia de um grande território em forma circular. Há poucos mapas atuais. Mas um documento português do século XVI traz uma breve descrição de um mapa antigo de origem javanesa que, aparentemente, mostrava muito do mundo. Também descreve as rotas de navegação dos chineses e outros povos do Pacífico. O mapa, propriamente, foi perdido, mas há uma análise a seu respeito em uma carta do almirante Afonso de Albuquerque para seu rei, dom Manuel, datada de 1º de abril de 1512.